2020
DOI: 10.1111/jscm.12215
|View full text |Cite
|
Sign up to set email alerts
|

Reinvigorating the Study of Opportunism in Supply Chain Management

Abstract: Opportunism is a core issue in supply chain management. However, assumption-omitted testing and a focus on general opportunism as opposed to specific forms of opportunism have stubbornly limited our understanding of this construct. Grounded in a review of empirical studies of opportunism, we identify empirical challenges that perpetuate conceptual limitations in the study of opportunism in supply chains. Hence, we provide suggestions about research designs and data sources that support an agenda that steers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 94 publications
3
54
0
Order By: Relevance
“…Supply chain digitalisation is an emerging field and so far, the overwhelming majority of research has focused on its 'bright side', while to our best knowledge, there are only a few papers discussing its potential dark side (e.g., Lumineau and Oliveira, 2020). Similarly, with regards to partner opportunism, the small number of existing studies, which are mostly conceptual in nature, have suggested that supply chain digitalisation (e.g., IoT and blockchain) would play a game-changing role in controlling partner opportunism by reducing information asymmetry and uncertainty related to exchanges (Saberi et al, 2019;Schmidt and Wagner, 2019).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supply chain digitalisation is an emerging field and so far, the overwhelming majority of research has focused on its 'bright side', while to our best knowledge, there are only a few papers discussing its potential dark side (e.g., Lumineau and Oliveira, 2020). Similarly, with regards to partner opportunism, the small number of existing studies, which are mostly conceptual in nature, have suggested that supply chain digitalisation (e.g., IoT and blockchain) would play a game-changing role in controlling partner opportunism by reducing information asymmetry and uncertainty related to exchanges (Saberi et al, 2019;Schmidt and Wagner, 2019).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…So far, the majority of research in this area has investigated the promises and benefits of supply chain digitalisation; in contrast, few studies have examined the dark sides of supply chain digitalisation, such as digital capability asymmetry and resulting increase in partner opportunism (Lumineau and Oliveira, 2020). In addition, the existing literature has acknowledged weak governance as a potential reason for such asymmetric gains in supply chain digitalisation (Bjorkdah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In our analyses, we found it both useful and impartial to turn opportunism into something to be established empirically instead of being assumed (cf. John, 1984; Lumineau & Oliveira, 2020). In the context of Indian Railways in particular, and risky long‐term contracting in general, we find it unfathomable that exchange partners would enter into a potentially long‐term relationship, but at the same time, assume that the other party is inclined to intentionally distort data and make self‐disbelieved promises.…”
Section: The Case Of Indian Railwaysmentioning
confidence: 99%
“…The methods used to evaluate and measure opportunistic behaviors at corporate enterprises for labor relations are discussed in detail in Popov and Ersh (2016); Pletnev and Kozlova (2020b). Lumineau and Oliveira (2019) carried out the detailed analysis of empirical studies of opportunism and proposed some solutions to improve the existing methods used to measure opportunism.…”
Section: Introductionmentioning
confidence: 99%